Comparative Analysis of Gut Microbial Composition and Functions in Przewalski’s Gazelle (Procapra przewalskii) From Various Habitats - Zhang, Jingjie; Gao, Hongmei; Jiang, Feng; Liu, Daoxin; Hou, Yuansheng; Chi, Xiangwen; Qin, Wen; Song, Pengfei; Cai, Zhenyuan; Zhang, Tongzuo (Frontiers in Microbiology, 2022)
Gut microbiota of mammals participates in host nutrient metabolism and plays an important role in host adaptation to the environment. Herein, to understand the relationship between environment differences and the composition and abundance of the gut microbiota of Przewalski's gazelle (Procapra przewalskii) in almost all its habitats, high throughput sequencing of the 16S rRNA gene was used to compared the characteristics of the gut microbiota based on total 120 fecal samples. The results showed that Przewalski's gazelle exhibited different characteristics of microbiota diversity in different habitats. The Jiangxigou Rescue Station (JX), Nongchang (NC), and Ganzihe and Haergai townships (GH) groups had a relatively high microbiota diversity, while the Niaodao scenic area (ND) group had the lowest diversity. This finding seemed to follow a similar pattern of change in the population of Przewalski's gazelle. Bacteroidetes and Actinobacteria were the phyla with significant differences, especially between the Wayu township (WY) and the other groups. The difference in the microbiota mainly included the Ruminococcaceae UCG-005, Christensenellaceae R-7 group, and Bacteroidaceae and was enriched in the ND, WY, and other regions. We speculated that the difference in the gut microbiota was due to a difference in environmental characteristics, particularly the food resources that the host can obtain. We speculated that a similar microbiome has important functions for species survival and represents the evolutionary commonality of Przewalski's gazelle, while a different microbiome plays an important role in the adaptation of Przewalski's gazelle to a different environment. The results of this study illustrate how the same species adapts to different environments from the perspective of gut microbiota plasticity, and therefore are of great significance for the protection and restoration of the population of this species.